Serial mediation of the relationship between impulsivity and suicidal ideation by depression and hopelessness in depressed patients - Xiaoli Chen; Shupeng Li (BMC Public Health, 2023)
Abstract Background Close relationships have been observed among impulsivity, depression, hopelessness, and suicidal ideation in depressed patients. However, the precise mechanism that connects these psychological symptoms remains unclear. This study aims to explore the mediation effect of depression and hopelessness on the relationship between impulsivity and suicidal ideation in depressed patients. Methods A total of 258 depressed patients were evaluated using the Hamilton Depression Scale, the Beck Hopelessness Scale, the Scale for Suicide Ideation, and the Barratt Impulsiveness Scale. A path analysis was afterwards performed to determine the specified relationships in the proposed model. Results The relationship between impulsivity and suicidal ideation was found to be serially mediated by depression and hopelessness. The mediating effect of depression and hopelessness accounted for 26.59% of the total effect. Specifically, in the pathway from impulsivity to hopelessness, the mediating effect of depression accounted for 40.26%. Moreover, the relationship between impulsivity and suicidal ideation was mediated by hopelessness, with the mediating effect accounting for 12.41%. It is important to note that these relationships were observed to be independent of age and marital status. Furthermore, the proposed model demonstrated a good fit with the data. Conclusions This study identified a serial mediation pathway between impulsivity and suicidal ideation, mediated by depression and hopelessness. Our findings indicate that impulsivity indirectly influences suicidal ideation through its association with depression, which subsequently contributes to feelings of hopelessness. These results emphasize the importance of addressing symptoms of depression and hopelessness in the prevention and intervention efforts targeting individuals with depression. Additionally, monitoring and addressing impulsivity levels may also be crucial in reducing the risk of suicidal ideation among this population. These findings provide valuable insights for future preventive programs and interventions aimed at mitigating suicidal ideation in individuals with depression.